Clinical characteristics and treatment approaches in patients with post-cholecystectomy syndrome due to remnant gallbladder (Annals of Medical Research, 2021)
Aim: A remnant gallbladder is a rare problem encountered in the diagnosis and treatment of the post-cholecystectomy syndrome. This study aimed to evaluate the clinical features and treatment modalities of patients with a symptomatic remnant gallbladder after cholecystectomy.Material and Methods: The data of 11 patients who were operated following the diagnosis of a remnant gallbladder between January 2013 and January 2019 were evaluated retrospectively. Clinical characteristics, diagnosis and treatment management, laparoscopy to open conversion rate and hospital stay were evaluated.Results: The median age was 55.3 years (range, 36 to 77 years), and the male/female ratio was 1/10. Right upper quadrant pain and jaundice were the most common symptoms. The time interval between cholecystectomy and symptom recurrence was 46.8 (range, 1 to 420) months. A remnant gallbladder was determined by ultrasonography in seven patients (63.6%) and by magnetic resonance cholangiopancreatography in 11 patients (100%). Preoperatively, ERCP was performed in six patients due to suspicion of stones in the main bile duct, except for the remnant gallbladder. Complementary cholecystectomy was performed by laparoscopically in seven patients, and only four patients had a conversion to open surgery. The median duration of hospital stay was four days (range, 2 to 9 days).Conclusion: The remnant gallbladder, which is the rare and a cause of the post-cholecystectomy syndrome, is a pathology that should be considered in patients with postoperative symptoms. Patients with a symptomatic remnant gallbladder should be treated with a multidisciplinary approach, including a careful choice of imaging modalities and surgical or endoscopic treatment methods.Keywords: Remnant gallbladder; post-cholecystectomy syndrome; diagnose; treatment.